(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Developing social competencies in future teachers is essential for creating positive and effective learning environments. This article explores key factors in nurturing these competencies, including emotional intelligence, communication skills, cultural competence, and teamwork, within the context of higher education. It emphasizes the importance of integrating these skills into teacher education programs to ensure that future educators are prepared for the dynamic challenges of modern classrooms. By fostering these abilities, teacher education institutions can contribute to the creation of more inclusive, empathetic, and collaborative educational settings that enhance both teaching and student success.